Sea bass hatchery operations. (Tigbauan, Iloilo, Philippines SEAFDEC, 1990)
Aquaculture Extension Manual No. 18 April 1998
Keywords: Aquaculture; Fish culture--Handbooks, Manuals, etc; Aquaculture--Handbooks, Manuals, etc; Sea basses